PENGEMBANGAN BAHAN AJAR TEMATIK TERPADU BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD KELAS V - Mardia Hi. Rahman; Saiful Latif (EDUKASI, 2020)
The 2013 curriculum suggests that learning must be integrated or commonly known as integrated thematic learning. Thematic learning in elementary schools usually combines material on several subjects into one theme. The references used by both teachers and students are provided by the government, namely teachers’ book and students’ book. The teachers directly teach their students using references provided without analyzing or further developing by the teacher. The implementation of 2013 curriculum requires teachers to be creative in using various learning models and scientific approaches. With these demands the teacher should be able to develop teaching materials in accordance with the learning model. This research is motivated by the importance of developing integrated thematic teaching materials based on Problem Based Learning models that are able to improve the critical thinking skills of fifth grade students. The study was conducted for 3 months. This type of research is development research refers to the 4-D model proposed by Thiagarajan, but this research is limited to defining, designing and developing. The instrument used to assess the quality of teaching materials is a questionnaire with five categories, while students' critical thinking skills use test instrument. Data analysis was performed by descriptive analysis. The results of the analysis show that integrated thematic teaching materials based on Problem Based Learning (PBL) on heat and its transfer are stated to meet valid criteria and practicality, because teaching materials are developed based on supporting theories consistently and can be used easily. Whereas in the effectiveness test of integrated thematic teaching materials based on problem based learning, it was declared effective to be used because the developed teaching materials had a positive impact in increasing students' critical thinking skills.